Hi‐C 3.0: Improved Protocol for Genome‐Wide Chromosome Conformation Capture. Issue 7 (19th July 2021) - Lafontaine, Denis L.; Yang, Liyan; Dekker, Job; Gibcus, Johan H.
Abstract: The intricate folding of chromatin enables living organisms to store genomic material in an extremely small volume while facilitating proper cell function. Hi‐C is a chromosome conformation capture (3C)‐based technology to detect pair‐wise chromatin interactions genome‐wide, and has become a benchmark tool to study genome organization. In Hi‐C, chromatin conformation is first captured by chemical cross‐linking of cells. Cells are then lysed and subjected to restriction enzyme digestion, before the ends of the resulting fragments are marked with biotin. Fragments within close 3D proximity are ligated, and the biotin label is used to selectively enrich for ligated junctions. Finally, isolated ligation products are prepared for high‐throughput sequencing, which enables the mapping of pair‐wise chromatin interactions genome‐wide. Over the past decade, "next‐generation" sequencing has become cheaper and easier to perform, enabling more interactions to be sampled to obtain higher resolution in chromatin interaction maps. Here, we provide an in‐depth guide to performing an up‐to‐date Hi‐C procedure on mammalian cell lines. These protocols include recent improvements that increase the resolution potential of the assay, namely by enhancing cross‐linking and using a restriction enzyme cocktail. These improvements result in a versatile Hi‐C procedure that enables the detection of genome folding features at a wide range of distances. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Fixation of nuclear conformation Basic Protocol 2 : Chromosome conformation capture Basic Protocol 3 : Hi‐C sequencing library preparation